VD_FINDINFO AP / 2013 / 22 vom 2. Dezember 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, ASSISTANCE JUDICIAIRE, RADIATION DU RÔLE | 109 al. 1 CPC (CH), 109 CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)